2007
DOI: 10.1177/026835550702200609
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Marginal Vein: Current Issues

Abstract: The marginal vein, an abnormal superficial vein of the lateral lower limb, is a remnant of primitive embryonic vessels that have failed to regress. According to the extent, topography and sites of connection with the deep veins, five types have been distinguished by Weber. The marginal vein is valveless and may create venous stasis. Limb-length discrepancy and nevus may coexist. Diagnosis is made by duplex scan examination and phlebography; angio computerized tomography or magnetic resonance effectively demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 2 publications
0
26
0
3
Order By: Relevance
“…In cases of deep vein hypoplasia, marginal vein can be resected since hypoplastic deep veins can spontaneously dilate to almost normal dimensions after marginal vein resection. In cases of deep venous aplasia, the embryonal vein can be the main drainage vein of the leg and resection is unlikely [11,21]. In cases with arteriovenous fistula, venous stasis increases in vessels causing valvular atresia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of deep vein hypoplasia, marginal vein can be resected since hypoplastic deep veins can spontaneously dilate to almost normal dimensions after marginal vein resection. In cases of deep venous aplasia, the embryonal vein can be the main drainage vein of the leg and resection is unlikely [11,21]. In cases with arteriovenous fistula, venous stasis increases in vessels causing valvular atresia.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with arteriovenous fistula, venous stasis increases in vessels causing valvular atresia. In these cases, venous skeletonisation may be performed by completely tying up the arterial inflow vessel [21]. Catheter-directed embolization using coils, particulates, or sclerotherapy may be performed in small arteriovenous fistulas [3].…”
Section: Discussionmentioning
confidence: 99%
“…(24) In particular, the persistent sciatic vein should be treated with sclerotherapy or embolization secondary to close proximity of the sciatic nerve. (24,29) Burrows et al reported their series of consecutive sclerotherapy patients with low flow vascular malformations and noted a good or excellent result in up to 90% of patients by clinical survey. However, there was a complication rate of 12% per treatment and a 28% complication rate per patient.…”
Section: Endovascular and Minimally Invasive Interventionmentioning
confidence: 99%
“…2) A marginal vein, an abnormal lateral, valveless vein of the lower limb has been treated with sclerosis, mainly with foam. However, because of the existence of huge perforants to the deep system, the technique can be dangerous (22).…”
Section: Sclerosis Techniques In Different Cvm Venous Malformationsmentioning
confidence: 99%